PENGARUH PAJAK TANGGUHAN, TAX TO BOOK RATIO, NET PROFIT MARGIN DAN OPERATING ASSETS TURNOVER TERHADAP KINERJA PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Prasetyo, Muji Wahyu; Wahyuni, Wiwin (Liability, 2019)
This study aimed to determine the effect of deferred tax, the tax-tobook ratio, net profit margin and asset turnover of the operating performance of the company in the manufacturing companies listed in Indonesia Stock Exchange. This study uses the Return on Investment (ROI) as a proxy of the company's performance. By using purposive sampling method was chosen by 38 companies manufacturing the period 2011-2012, a sample of this study. Tests using the classical assumption of normality test, heteroscedasticity, multicollinearity, and autocorrelation. Regression analysis was used in this research is multiple linear regression analysis.Based on the research results prove that the variable net operating profit margin and asset turnover significant positive effect on the performance of the company, while the tax-tobook ratio variable positive but not significant effect on the performance of the company and deferred tax variable but significant negative effect on the performance of the company.